Exploring the Impact of Oil Price Changes on Corporate Cash Holdings during VAT Era in UAE - Almaazmi, Ghada; Al-Shboul, Mohammad (International Journal of Energy Economics and Policy, 2025)
This study explores the impact oil price changes and corporate cash holdings during the VAE era. Using panel data analysis for 46 of the largest listed firms in the UAE stock markets, the study reveals that oil price changes adversely impact corporate cash holdings, confirming the transaction cost motive where firms are motivated to retain large amounts of cash to mitigate, among other transactions, the costs associated with oil price changes. However, the application of VAT after 2018 in UAE weakens the detrimental impact of oil price changes on the amount of cash held by corporations. This suggests that VAT plays a moderating role in reshaping the relationship between the cash held by the UAE corporations and oil price changes. However, when oil returns are divided into negative and positive returns, we find different results. During VAT era, firms tend to increase their cash holdings when oil returns are negative, while they tend to reduce the cash leak when oil returns are positive, arguing the application of the VAT system application enables firms to carefully manage their cash levels in order to reduce the decline in oil price. This research offers valuable insights for public authorities, managers, and shareholders by illustrating how oil price change can impact corporate cash holdings in an oil-exporting market during the VAT system. The results can guide policymakers and tax reformers in fostering sustainable financial and economic development.